Synthesis method of covalently bonded crystal lattice
Irreversible cross-coupling polymerization on a multifunctional substrate through Sonogashira coupling reaction, the problem of difficult synthesis of bulk γ-graphyne in the prior art was solved, and the synthesis of high-crystalline multi-layer γ-graphyne was achieved, which improved the expansion and stability of the material.
Patent Information
- Application Number
- CN202380072051.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-12
- Filing Date
- 2023-08-08
- Publication Date
- 2025-06-10
AI Technical Summary
The prior art is difficult to effectively synthesize bulk γ-graphyne, and the existing methods lack the scalability and stability, resulting in defects and limitations in the application of the materials.
Multilayer γ-graphyne was synthesized by irreversible cross-coupling polymerization on a multifunctional substrate using a method based on the Sonogashira coupling reaction. This method achieves self-corrected multi-site aggregation by forming multiple bonds in a single step by bypassing the dynamic dead end of partially connecting intermediates.
A high crystallinity multi-layer γ-graphyne was successfully synthesized, with good crystal uniformity and hexagonal symmetry of the material and few defects, which achieved improved material expansion and stability.
Smart Images

Figure CN120129654A_ABST
Abstract
Description
Cross - reference to related applications
[0001] This application claims priority to U.S. Provisional Application No. 63 / 397,416, filed on August 12, 2022, the entire content of which is incorporated herein by reference. Government sponsorship
[0002] This invention was made with government support under DE-SC0022100 awarded by the Department of Energy. The government has certain rights in this invention. Background Art
[0003] γ-Graphdiyne is the most symmetric sp 2 / sp 1 allotrope of carbon and can be regarded as graphene uniformly expanded by inserting two-carbon alkyne units. So far, the synthesis of bulk γ-graphdiyne remains difficult to achieve. Monolayer γ-graphdiyne is predicted to be a semiconductor with a moderate bandgap, its ultrafast carrier mobility is comparable to that of graphene, and it has high thermal conductivity and excellent strength. Due to these properties, γ-graphdiyne may become the basis for next-generation carbon-based electronics, photonics, and solar cells. Graphdiyne-based devices can be ultrathin, flexible, and operate at speeds unattainable by silicon chips. γ-Graphdiyne oligomers containing up to four dehydrobenzo
[12] annulene (12-DBA) repeating units have been prepared by multi-step organic synthesis, but until now, the extended crystal lattice has still been difficult to achieve.
[0004] Pyrolysis and chemical vapor deposition methods commonly used for the controlled synthesis of benzenoid carbon allotropes are not applicable to structures containing sp 1 because alkynes are easily converted to graphene or amorphous carbon at high temperatures. Although graphyne and graphyne-graphene heterostructures have been synthesized by templated solution-phase two-dimensional polymerization, similar methods have not been used for γ-graphdiyne. The reported graphyne synthesis relies on the Glaser-Hay sp 1 -sp 1 coupling polymerization of highly energetic hexaethynylbenzene, and this reaction can be conveniently carried out on a metal surface. A similar γ-graphdiyne synthesis requires coupling between sp 1 and sp 2 carbons, or the formation of three alkyne bonds from scratch for each 12-DBA repeating unit. The most common and widespread sp 1 -sp 2 C-C coupling method is the Sonogashira reaction. The mechanism of this reaction is considered to involve homogeneous Pd 0The catalytic cycle is similar to all other Pd-catalyzed cross-couplings. Therefore, attempts to confine this chemistry to the template surface are challenging. In addition, previously reported γ-graphyne oligomers distort planarity due to steric hindrance introduced by the terminal functional groups. This unavoidable distortion, together with the generally poor solubility of the oligomers, limits the stepwise extension of the lattice beyond 3–4 12-DBA units.
[0005] Hu et al., “Synthesis Ofγ-Graphyne Using Dynamic Covalent Chemistry.” Nat. Synth 1, 449–454 (2022), claim to have synthesized bulk γ-graphyne via a reversible alkyne metathesis reaction. However, this approach is not scalable because the key precursors 1,2,3,4,5,6-hexa[2-(4-hexylphenyl)ethynyl]benzene (HHEB) and 1,2,3,4,5,6-hexapropynylbenzene (HPB) are both unstable and extremely difficult to synthesize. These compounds are closely related to hexaethynylbenzene, which is notorious for being explosive on contact and has never been isolated or handled in pure form for this reason. The γ-graphyne described by Hu et al. always features n-hexyl edge groups, which is unfavorable for further edge elaboration or the use of the material in devices. In addition, Hu’s manuscript shows that only reversible reactions can be used to prepare this type of material. The presence of the catalyst at the later stages of this reversible reaction may introduce undesirable defects in the material, including but not limited to interlayer cross-links. Summary of the invention
[0006] Embodiments described herein relate to methods for synthesizing covalently bonded lattices based on irreversible bonding reactions that facilitate radical substitution on multifunctional substrates, and in particular to the preparation or synthesis of multilayered γ-graphene (sp 2 / sp 1 Here we show that multifunctional 1,3,5-trihalo-2,4,6-triethynylbenzene monomers can be polymerized to extended γ-graphene under appropriately tuned Sonogashira coupling conditions. The main idea guiding our thinking is that an efficient route to graphene and similar rigid 2D polymers could proceed either via reactions that form multiple bonds in a single step or via a series of kinetically coupled rapid steps. Such a mechanism would bypass the kinetic dead end of partially linked intermediates that has limited all previously described syntheses. Furthermore, this type of multisite polymerization would be self-correcting. Defects in the growing lattice would be the most reactive sites due to local distortions and strains, and these defects could be relieved by multisite reactions with monomers.
[0007] In some embodiments, a Sonogashira cross-coupling reaction between a terminal alkyne and an aryl halide is a bond-forming reaction that favors complete reactivity on a multifunctional substrate.
[0008] In some embodiments, the reactant for synthesizing a covalently bonded lattice can be any possible 1,3,5-trihalo-2,4,6-triethynylbenzene, which is symmetric or asymmetric, and wherein the halogen is any one of Cl, Br, or I.
[0009] In other embodiments, the reactant for synthesizing a covalently bonded lattice can be any possible ((2,4,6-trihalobenzene-1,3,5-triyl)tris(ethyne-2,1-diyl))tris(trimethylsilane), which is symmetric or asymmetric, and wherein the halogen is any one of Cl, Br, or I.
[0010] The Sonogashira cross-coupling reaction is carried out using a palladium catalyst. The palladium source can be selected from palladium black, palladium on carbon, palladium(π-cinnamyl)chloride dimer, bis(triphenylphosphine)palladium(II) dichloride, bis(benzonitrile)palladium(II) chloride, bis(triphenylphosphine)palladium(II) diacetate, tetrakis(triphenylphosphine)palladium(0), bis(dibenzylideneacetone)palladium(0), tris(dibenzylideneacetone)dipalladium(0), dichlorobis(tricyclohexylphosphine)palladium(II), dichlorobis(tris(o-tolyl)phosphine)palladium(II), allylpalladium(II) chloride dimer, (2-methylallyl)palladium(II) chloride dimer, (1,3-bis(2,6-diisopropylphenyl)imidazolidin-2-yl)(3-chloropyridyl)palladium(II) dichloride, (1,3-bis(2,6-dimethylphenyl)imidazolidin-2-yl)(3-chloropyridyl)palladium(II) dichloride, [1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene](3-chloropyridyl)palladium(II) dichloride, palladium(II) 2,4-pentanedionate, or any possible alkali metal salt of tris(3,3',3”-phosphinidynetris(benzenesulfonic acid)palladium(0).
[0011] The Sonogashira cross-coupling reaction can also be carried out using a copper cocatalyst. The copper cocatalyst can be selected from copper(I) iodide, copper(I) chloride, copper(I) bromide, copper(I) tetra(acetonitrile) hexafluorophosphate, copper(I) tetrafluoromethanesulfonate, copper(0) foil or chips in combination with pyridine, copper(0) foil or chips in combination with any aliphatic tertiary amine, or copper(II) sulfate in combination with sodium ascorbate.
[0012] In some embodiments, the reactant, palladium catalyst, and copper cocatalyst are provided in a solvent. The solvent can be selected from pyridine, tetrahydrofuran, a mixture of tetrahydrofuran and N,N-diisopropylethylamine, toluene, benzene, water, a mixture thereof, or a biphasic mixture of water and an immiscible organic solvent.
[0013] In some embodiments, the loading of the Pd catalyst can be from 0.5 mol% to 120 mol% relative to a reactant such as 1,3,5-trihalo-2,4,6-triethynylbenzene.
[0014] In other embodiments, the loading of the Cu cocatalyst can be from 0.1 mol% to 10 mol% relative to a reactant such as 1,3,5-trihalo-2,4,6-triethynylbenzene.
[0015] In some embodiments, the reaction is carried out at a reaction temperature of about 60 °C to about 130 °C.
[0016] In some embodiments, the reaction is carried out in the presence of a soluble fluoride salt.
[0017] In some embodiments, the ordered two-dimensional polymerization occurs in the absence of a substrate or an added template.
[0018] In some embodiments, multilayer γ-graphyne is synthesized, and the linear dimension of its crystal domains is in the range of 10 nanometers to 500 micrometers.
[0019] In other embodiments, few-layer (e.g., 1-25 layers) γ-graphyne is synthesized, and the linear dimension of its crystalline flakes is in the range of 10 nanometers to 500 micrometers. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] FIG. 1 (A-E) shows allotropes of carbon. (A) Graphite, graphene, zigzag nanotubes, and buckminsterfullerene C60. (B) Cumulene network. (C) x,y,z-graphyne. 12,12,12-graphyne and 6,6,12-graphyne. (D) Graphyne-n (graphdiyne, n = 2). (E) Graphyne (or γ-graphyne).
[0021] FIG. 2 (A-G) shows the two-dimensional polymerization of TBETB. (A) Overview of the selected reaction conditions. (B-D) Representative bright-field TEM, SAED, and SEM of carbon sheets obtained by the Pd(PPh 3 ) 4 / Cu foil reaction. (E-G) Representative bright-field TEM, SAED, and SEM of carbon sheets obtained by the Pd(PPh 3 ) 4 / CuI protocol.
[0022] FIG. 3 (A-D) shows high-resolution XPS data in the C1s peak region. (A) By Pd(PPh 3 ) 4Carbon sheets obtained by the CuI method. (B) Carbon sheets obtained by the Pd(PPh 3 ) 4 / Cu foil method. (C) Control experiment carried out using only Pd(PPh 3 ) 4 . (D) Control experiment without a catalyst.
[0023] Figure 4 Shows the 13 C NMR spectrum of 1,3,5-tribromo-2,4,6-triiodobenzene in DMSO-d6.
[0024] Figure 5 Shows the 3 H NMR spectrum of ((2,4,6-tribromobenzene-1,3,5-triyl)tris(ethyne-2,1-diyl))tris(trimethylsilane) in CDCl 1 .
[0025] Figure 6 Shows the 3 C NMR spectrum of ((2,4,6-tribromobenzene-1,3,5-triyl)tris(ethyne-2,1-diyl))tris(trimethylsilane) in CDCl 13 .
[0026] Figure 7 Shows the 1 H NMR spectrum of 1,3,5-tribromo-2,4,6-triethynylbenzene (TBTEB) in DMSO-d6.
[0027] Figure 8 Shows the 13 C NMR spectrum of 1,3,5-tribromo-2,4,6-triethynylbenzene (TBTEB) in DMSO-d6.
[0028] Figure 9 Shows the FTIR (ATR-FTIR on diamond) of 1,3,5-tribromo-2,4,6-triiodobenzene.
[0029] Figure 10 Shows the FTIR (ATR-FTIR on germanium) of ((2,4,6-tribromobenzene-1,3,5-triyl)tris(ethyne-2,1-diyl))tris(trimethylsilane).
[0030] Figure 11 Shows the FTIR (ATR-FTIR on germanium) of 1,3,5-tribromo-2,4,6-triethynylbenzene (TBTEB).
[0031] Figure 12 Shows for Table 1 entry 1 (TBTEB and Pd(PPh3 ) 4 XPS survey corresponding to (TBTEB and Pd(PPh
[0032] Figure 13 Showed the one corresponding to Entry 2 in Table 1 (TBTEB and Pd(PPh 3 ) 4 / Cu foil in pyridine).
[0033] Figure 14 Showed the one corresponding to Entry 3 in Table 1 (TBTEB and Pd(PPh 3 ) 4 In pyridine, without Cu).
[0034] Figure 15 Showed the XPS survey corresponding to Entry 4 in Table 1 (thermal decomposition of TBTEB in refluxing pyridine).
[0035] Figure 16 (A - D) showed the high - resolution XPS data in the C1s peak region. (A) Entry 1 in Table 1 (TBTEB and Pd(PPh 3 ) 4 / CuI in pyridine). (B) Entry 2 in Table 1 (TBTEB and Pd(PPh 3 ) 4 / Cu foil in pyridine). (C) Entry 3 in Table 1 (TBTEB and Pd(PPh 3 ) 4 In pyridine, control experiment without Cu). (D) Entry 4 in Table 1 (control experiment without catalyst).
[0036] Figure 17 (A - D) showed the high - resolution XPS spectra in the Br 3d region of the selected carbon material samples. (A) Entry 1 in Table 1 (TBTEB and Pd(PPh 3 ) 4 / CuI in pyridine). (B) Entry 2 in Table 1 (TBTEB and Pd(PPh 3 ) 4 / Cu foil in pyridine). (C) Entry 3 in Table 1 (TBTEB and Pd(PPh 3 ) 4 In pyridine, control experiment without Cu). (D) Entry 4 in Table 1 (control experiment without catalyst).
[0037] Figure 18 (A - B) showed: (A) Photograph of the carbon material corresponding to Entry 1 in Table 1 (TBTEB and Pd(PPh 3 ) 4 / CuI in pyridine). (B) Photograph of the carbon material corresponding to Entry 2 in Table 1 (TBTEB and Pd(PPh3 ) 4 The carbon material photo corresponding to ( / Cu foil in pyridine).
[0038] Figure 19 (A - D) shows the representative bright - field TEM images of the carbon products corresponding to Entry 1 in Table 1 (TBTEB and Pd(PPh 3 ) 4 / CuI in pyridine).
[0039] Figure 20 (A - F) shows the representative bright - field TEM images of the carbon products corresponding to Entry 2 in Table 1 (TBTEB and Pd(PPh 3 ) 4 / Cu foil in pyridine). (E - F) Representative SAED ring patterns of the same material.
[0040] Figure 21 (A - C) shows the representative bright - field TEM images of the carbon products corresponding to Entry 3 in Table 1 (TBTEB and Pd(PPh 3 ) 4 In pyridine, a control experiment without Cu).
[0041] Figure 22 (A - C) shows the representative bright - field TEM images of the carbon products corresponding to Entry 4 in Table 1 (Thermal decomposition of TBTEB in refluxing pyridine).
[0042] Figure 23 (A - B) shows the representative SEM images of the carbon products corresponding to Entry 2 in Table 1 (TBTEB and Pd(PPh 3 ) 4 / Cu foil in pyridine).
[0043] Figure 24 (A - H) shows the possible stacking patterns of γ - graphdiyne sheets and their simulated SAED patterns in the c - orientation (sheets perpendicular to the incident beam). The inter - atomic distances are obtained by DFT calculations.
[0044] Figure 25 (A - H) shows the possible stacking patterns of γ - graphdiyne sheets and their simulated SAED patterns when rotated 45° from the (0001) pole to the observation direction (matching the 45° rotation of the experimental diffraction pattern). The inter - atomic distances are obtained by DFT calculations.
[0045] Figure 26 (A - H) shows the possible stacking patterns of γ - graphdiyne sheets and their simulated SAED patterns in the b - orientation (sheets parallel to the incident beam). The inter - atomic distances are obtained by DFT calculations.
[0046] Figure 27 Shows the DFT - generated potential energy surface of the binding of the TBTEB monomer to the γ - graphdiyne monolayer. Detailed Description of the Invention
[0047] Unless otherwise indicated, all scientific and technical terms used in this application have the meanings commonly used in the art. The definitions provided herein are intended to facilitate the understanding of certain terms frequently used herein and are not intended to limit the scope of this application.
[0048] As used herein, the articles "a" and "an" refer to one or more than one (i.e., at least one) of the grammatical objects of the article. For example, "an element" means one element or more than one element.
[0049] The term "about" will be understood by those of ordinary skill in the art and will vary depending on the context in which it is used.
[0050] When a part "comprises" a component, unless otherwise disclosed, it means that the part may further comprise another component without excluding the other component.
[0051] The term "combinations thereof" contained in a Markush representation means one or more mixtures or combinations selected from the group consisting of the components described in the Markush representation and means including at least one component selected from the group consisting of the said components.
[0052] The term "A and / or B" means "A or B, or A and B".
[0053] Throughout this disclosure, various aspects of the invention may be presented in a range format. It should be understood that the description in range format is merely for convenience and brevity and should not be construed as a strict limitation on the scope of the invention. Thus, the description of a range should be considered to specifically disclose all possible sub-ranges within that range as well as the individual numerical values within that range. For example, the description of a range from 1 to 6 should be considered to specifically disclose sub-ranges such as 1 to 3, 1 to 4, 1 to 5, 2 to 4, 2 to 6, 3 to 6, etc., and the individual and partial numerical values within that range, such as 1, 2, 3, 4, 5, 5.5, and 6. This applies regardless of the breadth of the range.
[0054] The embodiments described herein relate to methods for synthesizing covalently bonded lattices based on irreversible bonding reactions that favor complete substitution on polyfunctional substrates, and particularly relate to the preparation or synthesis of multilayer γ-graphdiyne by crystallization-assisted irreversible cross-coupling polymerization (carbon sp 2 / sp 1Method for preparing allotropes. We found that under appropriately adjusted Sonogashira coupling conditions, polyfunctional 1,3,5-trihalo-2,4,6-triethynylbenzene monomers can be polymerized into extended γ-graphyne. The main concept guiding our thinking is that an effective route to graphyne and similar rigid two-dimensional polymers can be achieved through reactions that form multiple bonds in a single step or through a series of rapidly kinetically coupled steps. This mechanism would bypass the kinetic dead ends of partially connected intermediates that limit all previously described syntheses. Additionally, this type of multi-site polymerization would be self-correcting. Due to local distortions and strains, defects in the growing lattice would become the most reactive sites, and these defects could be alleviated through multi-site reactions with monomers.
[0055] In some embodiments, the bonding reaction is a Sonogashira cross-coupling reaction between a terminal alkyne and an aryl halide. Each terminal alkyne group is capable of cross-coupling with the halogen group of an aryl halide through a Sonogashira cross-coupling reaction, thereby forming a network of such reactants connected by acetylene groups. γ-Graphyne can consist of triple-bond (sp) and double-bond (sp2) carbon atoms arranged in a benzene ring lattice connected by acetylene bonds and having an atom-thick planar structure.
[0056] In some embodiments, the reactants for synthesizing the covalently bonded lattice can be any possible 1,3,5-trihalo-2,4,6-triethynylbenzene, which can be symmetric or asymmetric, and wherein the halogen is any one of Cl, Br, or I. For example, the trihalotriethynylbenzene can be 1,3,5-tribromo-2,4,6-triethynylbenzene or 1,3,5-trichloro-2,4,6-triethynylbenzene.
[0057] In other embodiments, the reactants for synthesizing the covalently bonded lattice can be any possible ((trihalobenzenetriyl)tris(ethynediyl))tris(trimethylsilane), which can be symmetric or asymmetric, and wherein the halogen is any one of Cl, Br, or I. For example, ((trihalobenzenetriyl)tris(ethynediyl))tris(trimethylsilane) can be ((2,4,6-tribromobenzene-1,3,5-triyl)tris(ethyne-2,1-diyl))tris(trimethylsilane).
[0058] In some embodiments, the catalyst can be a palladium compound. The palladium source can be selected from palladium black, palladium on carbon, palladium(π-cinnamyl) chloride dimer, bis(triphenylphosphine)palladium(II) dichloride, bis(benzonitrile)palladium(II) chloride, bis(triphenylphosphine)palladium(II) diacetate, tetrakis(triphenylphosphine)palladium(0), bis(dibenzylideneacetone)palladium(0), tris(dibenzylideneacetone)dipalladium(0), dichlorobis(tricyclohexylphosphine)palladium(II), dichlorobis(tri-o-tolylphosphine)palladium(II), allylpalladium(II) chloride dimer, (2-methylallyl)palladium(II) chloride dimer, (1,3-bis(2,6-diisopropylphenyl)imidazolidine)(3-chloropyridyl)palladium(II) dichloride, (1,3-bis(2,6-dimethylphenyl)imidazolidine)(3-chloropyridyl)palladium(II) dichloride, [1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene](3-chloropyridyl)palladium(II) dichloride, palladium(II) 2,4-pentanedionate, or any possible alkali metal salt of tris(3,3',3”-phosphinidynetri(benzenesulfonic acid)palladium(0).
[0059] In other embodiments, the catalyst can include a copper cocatalyst. The copper cocatalyst can be selected from copper(I) iodide, copper(I) chloride, copper(I) bromide, copper(I) tetra(acetonitrile) hexafluorophosphate, copper(I) tetraacetonitrile trifluoromethanesulfonate, copper(0) foil or chips complexed with pyridine, copper(0) foil or chips complexed with any aliphatic tertiary amine, or copper(II) sulfate complexed with sodium ascorbate.
[0060] In some embodiments, the reactants, palladium catalyst, and copper cocatalyst are provided in a solvent. The solvent can be selected from pyridine, tetrahydrofuran, a mixture of tetrahydrofuran and N,N-diisopropylethylamine, toluene, benzene, water, combinations thereof, or a biphasic mixture of water and an immiscible organic solvent.
[0061] In one example, the Sonogashira cross-coupling reaction can be carried out in a solution or mixture containing the reactants, palladium catalyst, and copper cocatalyst. In some embodiments, the palladium catalyst is Pd(PPh 3 ) 4 , and the copper cocatalyst is CuI. This solution can be prepared by dissolving the solid Pd(PPh 3 ) 4 and CuI in a solvent mixture. The solvent mixture can include an amine base and an organic solvent. For example, the amine base can include pyridine or triethylamine, and the organic solvent can include toluene.
[0062] In some embodiments, the reaction can also be carried out in the presence of a soluble fluoride salt.
[0063] In some embodiments, the loading of the Pd catalyst in the reaction mixture can be from about 0.5 mol% to about 120 mol% relative to reactants such as 1,3,5-trihalo-2,4,6-triethynylbenzene. For example, the Pd catalyst can be from about 25 mol% to about 115 mol%, from about 50 mol% to about 110 mol%, or from about 75 mol% to about 105 mol% (e.g., about 100 mol%) relative to the reactants.
[0064] In other embodiments, the loading of the Cu cocatalyst in the reaction mixture can be from about 0.1 mol% to about 10 mol% relative to reactants such as 1,3,5-trihalo-2,4,6-triethynylbenzene. For example, the Cu cocatalyst can be from about 1 mol% to about 8 mol%, from about 2 mol% to about 7 mol%, or from about 3 mol% to about 6 mol% (e.g., about 4 mol%) relative to the reactants.
[0065] In some embodiments, a reaction solution or mixture comprising reactants, a palladium catalyst, a copper cocatalyst, a solvent, and optionally a soluble fluoride salt can be heated to a certain temperature for a certain period of time to effectively produce a covalently bonded lattice and / or multilayer γ-graphyne. In some embodiments, the reaction is carried out in an inert atmosphere under vacuum, the reaction temperature is from about 60 °C to about 130 °C, and the duration can be at least about 1 hour, at least about 12 hours, at least about 24 hours, at least about 48 hours, or at least about 72 hours (e.g., 72 hours).
[0066] In some embodiments, ordered two-dimensional polymerization occurs in the absence of a physical substrate or an externally added template, which includes a surface on which two-dimensional polymerization may occur. Such a physical substrate may include a metal foil, fiber, or particle, which defines a surface on which polymerization may occur.
[0067] The synthesized covalently bonded lattice and / or multilayer γ-graphyne can be separated and / or removed from the reaction solution and rinsed multiple times (e.g., 5 times) with a solvent such as ethanol to remove any residues remaining on the surface of the synthesized covalently bonded lattice and / or γ-graphyne material.
[0068] In some embodiments, the synthesized graphyne can have near-perfect crystal uniformity and / or near-perfect hexagonal crystal symmetry, with very few or no defects. Graphyne can also have a ratio of sp 1 carbons to sp 2 carbons of 1:1 in the crystal material.
[0069] In some embodiments, multilayer γ-graphyne is synthesized, and the linear dimension of its crystal domains ranges from about 10 nanometers to about 500 micrometers. For example, the linear dimension of the crystal domains can be from about 10 nanometers to about 500 micrometers, from about 50 nanometers to about 100 micrometers, from about 100 nanometers to about 50 micrometers, or from about 500 nanometers to about 10 micrometers.
[0070] In other embodiments, few-layer (e.g., 1-25 layers) γ-graphyne is synthesized, and the linear dimension of its crystal flakes ranges from 10 nanometers to 500 micrometers.
[0071] Some other embodiments relate to γ-graphyne in which the linear dimension of the crystal domains ranges from 10 nanometers to 500 micrometers.
[0072] In some embodiments, γ-graphyne may include polyfunctional reactive groups at the edges of the γ-graphyne. These polyfunctional reactive groups can be selected from alkyne and halogen groups.
[0073] Other embodiments described herein relate to graphyne prepared by the methods described herein.
[0074] The γ-graphyne material can be used in various applications, including energy, environmental, and biomedical applications. For example, the γ-graphyne material can be used in applications for adsorbing, capturing, and separating carbon dioxide, carbon monoxide, ammonia, sulfur dioxide, and other gases, adsorbing organic substances such as polymer chains and acrolein, selectively filtering and purifying water, seawater separation and desalination, as a single-atom catalytic substrate for noble metals, stabilizing noble metal catalysis, and detecting toxic and harmful substances such as hydrogen peroxide, carbon monoxide, and toxic gases. Biomedical applications include applications for amino acid detection, regulating the structure and properties of calmodulin, and promoting the extraction of cholesterol from proteins. Energy applications can include electrochemical energy storage, hydrogen storage, high-density magnetic storage, as a thermoelectric material, manufacturing of electronic and / or photonic devices (e.g., nonlinear optical devices), rechargeable batteries, or organic solar cells. Further other applications can also include for ultra-high strength composite materials and as a catalyst. In addition, the γ-graphyne material can also be used in solar cells, lithium batteries, photocatalysis, oxygen reduction, field emission performance, and real-time detection of DNA.
[0075] For example, due to its regular pore structure and unique electronic properties, the nanoscale pores of γ-graphyne can be used to accommodate ions for energy storage, while the highly π-conjugated electron-rich framework can provide d-π interactions with transition metals to prepare single-atom catalysts.
[0076] Hydrogen storage is another potential application of the γ-graphyne material. The Kubas interaction refers to the interaction between the d orbital and H 2Hybridization of the σ / σ* orbitals of the molecule, which is known to enhance the H 2 binding energy. Calcium ions can also interact with H 2 molecules to produce Kubas interactions. It was previously found that γ-graphyne can be used as a support material to disperse calcium ions, effectively suppressing the aggregation or clustering of these ions, which is crucial for maintaining the H 2 storage capacity. Lu, Na, and Ti atoms are also supported on γ-graphyne, which can provide enhanced hydrogen storage capacity.
[0077] The strong d-π interaction between γ-graphyne and metal atoms enables γ-graphyne to be used in γ-graphyne-supported transition metal / noble metal (NM) single-atom catalysts. The binding energy of noble metal single atoms on γ-graphyne is significantly greater than that on graphene because the p / p* orbitals of the triple bond can directly point to the metal atoms. The γ-graphyne-supported Fe single-atom catalyst exhibits high catalytic activity for CO oxidation, and this reaction proceeds through the Eley-Rideal mechanism with a low energy barrier. In acidic media, the γ-graphyne-supported Fe and Co single-atom catalysts can catalyze the oxygen reduction reaction through an efficient four-electron reduction mechanism. The γ-graphyne-supported Cu single-atom catalyst shows catalytic efficiency for the CO 2 electroreduction and hydrogen evolution reactions. Similarly, Ru-modified γ-graphyne can efficiently catalyze the CO reduction reaction through the Langmuir-Hinshelwood pathway.
[0078] The following examples are for illustrative purposes only and are not intended to limit the scope of the appended claims. Examples
[0079] In this example, we demonstrated that under appropriately adjusted Sonogashira coupling conditions, the A 3 B 3 type monomer 1,3,5-tribromo-2,4,6-triethynylbenzene (TBTEB, Figure 2) can be polymerized into extended γ-graphyne. Materials and methods Materials
[0080] All reagents and solvents were obtained from commercial suppliers (Acros Organics, Sigma-Aldrich, TCI Chemicals, Fisher Scientific, Oakwood Chemical, and VWR International) and were used without further purification unless otherwise stated. Tetrahydrofuran (THF) was distilled over Na / diphenylketone. Triethylamine (TEA) was distilled over CaH 2Distillation. Anhydrous pyridine (Py) was purchased from Acros (AcroSeal package) and used without further purification. Copper foil, 1.0 mm thick, Puratronic 99.999% (metal basis), with a lateral size of 25 × 50 mm, was purchased from Alfa Aesar and cut into pieces of 5 × 10 mm. These pieces were then sonicated in 3M HCl, water, ethanol, and acetone for 20 minutes, dried under high vacuum at ambient temperature, and used immediately. Synthesis methods
[0081] The reactions were monitored by thin-layer chromatography (TLC) on 0.25 mm MilliporeSigma aluminum-backed silica gel plates (60F-254). The plates were visualized using 254 nm ultraviolet light and an alkaline potassium permanganate staining solution (1.5 g KMnO 4 in 150 ml of water, 0.5 g NaOH, and 10 g K 2 CO 3 ; terminal alkynes stain yellow). Flash chromatography was performed on Luknova SuperSepTM (230 - 400 mesh) silica gel. Reactions that required anhydrous or air-free conditions were carried out using standard Schlenk line techniques under a positive pressure of N 2 or Ar. Nuclear magnetic resonance (NMR) spectra
[0082] 1H NMR spectra were recorded on a Bruker Avance III HD 500 spectrometer operating at 500.24 ([[]]END]] 1 H), 125.79 ([[]]END]] 13 C), or 99.37 ([[]]END]] 29 Si) MHz, equipped with a Bruker Ascend 500 MHz US Narrow Bore Magnet and a BroadbandProdigy TCI CryoProbe. 1H NMR spectra were referenced to TMS ([[]]END]] 1 H, [[[]]END]] 13 C, [[[]]END]] 29 Si) or the residual solvent peak. Chemical shifts (δ) were reported in parts per million (ppm). Gas chromatography - mass spectrometry
[0083] GC-MS analysis was performed on an Agilent 5977B GC / MSD instrument equipped with an Agilent 7890B auto liquid sampler. Before sample injection, a 10 μL syringe was cleaned with acetone and ethyl acetate (3×10 μL each). Then 1 μL of the sample was automatically injected into the instrument. The method used a 3-minute solvent delay. The oven was initially set at 60 °C and held at this temperature for 2.25 minutes, then the temperature was raised to 225 °C at a rate of 35 °C / min. Data analysis was performed using Agilent MassHunter Qualitative Analysis Navigator. Infrared spectroscopy
[0084] Conventional small molecule FTIR spectra were collected on an Agilent Cary 630 FTIR instrument equipped with a single reflection germanium or diamond attenuated total reflection (ATR) module. Before sampling, the instrument was calibrated against a newly cleaned (acetone) and dried crystal surface. Solid samples were placed directly on the crystal and fixed with a needle press. 32 scans from 4000 to 550 cm -1 were recorded. Backgrounds (512 scans) were collected for each sample. Melting point
[0085] Melting points were determined using a Mettler Toledo MP50 Melting Point System. Preparation of exfoliated samples
[0086] Dispersions (1 mg / mL) of the analyte in water were prepared by sonication using a Branson SFX550 Sonifier. A 1 / 8" double stepped microtip (Branson p / n 101-063-212) was used. Samples were treated at 50% amplitude for 15 minutes. Scanning electron microscopy (SEM)
[0087] Figure 2G The SEM images in Figure 23 were acquired on a FEI Apreo 2 SEM operating at 5 kV and a FEI Inspect F-50 operating at 30 kV, respectively. For these images, the dried material was added to a carbon tape and mounted on an SEM sample holder and sputter-coated with a thin layer of gold. Transmission electron microscopy (TEM) and selected area electron diffraction (SAED)
[0088] The exfoliated samples were analyzed by TEM. Before sample preparation, 200-CuC-B grids were plasma treated for 30 s using an Emitech K100× glow discharge unit. 3 μL of the sample dispersion was added to the grid and adsorbed for 5 min, then the excess solvent was aspirated. The grid was transferred to a single-tilt sample holder and imaged on a FEI Tecnai 20 TEM operating at 200 kV in low-dose mode. Images were recorded on a Tvips F416. Data were collected using SerialEM software. Tilting was performed using the equipped α rotary goniometer.
[0089] SAED patterns were recorded on a FEI Tecnai 20 TEM using a 40 μm selected area aperture and without a selected area aperture. The obtained patterns were calibrated on a 3 mm grid relative to the (111) plane of evaporated aluminum (interplanar spacing 0.2338 nm). The calibration sample was purchased from Electron Microscopy Sciences (EMS p / n 80044). X - rays X - ray photoelectron spectroscopy (XPS)
[0090] The samples were spread on double-sided copper tape for XPS analysis. Survey and high-resolution spectra were acquired on a PHI VersaProbe II Scanning XPS Microprobe using monochromatic Al X-rays at a pressure of 10 -10 to 10 -7 Torr. The data were smoothed using the Savitzky-Golay method with a smoothing width of 5 and analyzed using CasaXPS software.
[0091] Before deconvolution, a Tougaard background was applied to each peak. All peak fittings used a generalized Voigt-like peak shape because this function best fits asymmetric XPS signals. CasaXPS provides the generalized Voigt function, described as LorentzianFinite:LF(α,β,w,n,m), where the first three parameters (α,β,w) affect the Lorentzian line shape and its asymmetry, and the last two parameters (n,m) change the width of the Gaussian function and the number of convolutions with the Lorentzian component. Symmetric peak parameters were used for LF line shape fitting: LF(1,1,255,360,6), and these values were derived from the default symmetric peak shape settings in CasaXPS. The full width at half maximum (FWHM) of all sub-peaks was constrained to 1.6 eV or less. The sub-peaks were located at 283.7 eV (terminal alkyne sp 1 ), 284.6 eV (aromatic sp 2 ), 285.3 eV (internal alkyne sp 1)、286.9 eV (aromatic C-Br) and 288.5 eV (carbonyl C=O). All peaks allow a peak position fluctuation of ±0.2 eV. Calculations and modeling Density functional theory (DFT) calculations
[0092] All DFT calculations were carried out using the RIPER module of TURBOMOLE / 7.5 with two-dimensional periodic boundary conditions. In all cases, the PBE density functional was used, with D3 dispersion correction and Becke-Johnson damping. All calculated geometries are generally consistent with previous computational studies on γ-graphyne.
[0093] The potential energy surfaces of γ-graphyne bilayers and single molecule / graphyne supercells were calculated as a function of the horizontal offset of the upper γ-graphyne layer or molecule relative to the lower layer, with the interlayer distance fixed at The binding energy of each structure was calculated as the adsorption energy (EE 结合 = EE 双层 – EE 分离 ). For the γ-graphyne bilayer structure, a 9×9 k-point mesh was used. The monomer / graphyne supercell was constructed using a 3×3 γ-graphyne monolayer to ensure a spacing of 1 nm between periodic images of adjacent monomers. Due to the periodicity of these resulting supercells, a coarser 3×3 k-point mesh was used in the entire potential energy surface scan calculation. The def2-SVP basis set was used throughout the calculation.
[0094] The local bilayer minima identified from the potential energy surface were refined by geometric optimization using the def2-TZVP basis set and a 9×9 k-point mesh. Similarly, the selected binding site supercell structures were optimized using def2-SVP and a 9×9 k-point mesh. Finally, the binding energies of all structures were also calculated using def2-TZVP and a finer 17×17 k-point mesh. SAED simulations
[0095] The lattice parameters and bond lengths were obtained from DFT calculations (see above) and previously published computational studies. SAED and PXRD simulations were performed using the CrystalMaker software suite. A model of a single-layer γ-graphyne sheet was constructed in CrystalMaker using the hexagonal P6 lattice, with the parameters a and c set to and The asymmetric unit includes four atoms located at 0.208, 0.412, 0.589, and 0.795 along the hexagonal P6 x-axis. Basic models corresponding to different layer stacking patterns were constructed using Vesta. Small molecule synthesis 1,3,5 - Tribromo - 2,4,6 - triiodobenzene
[0096] The synthesis procedure of 1,3,5-tribromo-2,4,6-triiodobenzene was adjusted from the literature. During 15 min, at room temperature (rt), periodic acid (41.03 g, 180 mmol) was added portionwise to concentrated sulfuric acid (500 mL). After the periodic acid was dissolved, powdered KI (89.64 g, 540 mmol) was added portionwise at 0 °C over 1 h. During 25 min, at 0 °C, 1,3,5-tribromobenzene (18.89 g, 60.0 mmol) was added portionwise to the resulting dark purple solution. After the solution was stirred at room temperature for 72 h, the resulting thick mixture was poured onto ice. The obtained precipitate was filtered and washed with H 2 O (5 × 200 mL), and then washed with methanol (MeOH) (5 × 200 mL). The product was recrystallized twice from pyridine / ethanol (EtOH) 1:4 (1000 mL) to obtain a solid. The solid was dried under high vacuum for 1 day to obtain 1,3,5-tribromo-2,4,6-triiodobenzene 2 (28 g, 67%) as a pale yellow solid. Mp > 300 °C (decomp.); FTIR (neat) νmax = 1488, 1354, 1262, 1227, 1147, 1002, 858, 771, 739, 554, 508 cm -1 . 13 C NMR (126 MHz, DMSO-d6) δ 138.61 (CBr), 108.23 (CI). EI-MS fragmentation: m / z 695.5, 693.5, 691.5, 689.5, 567.6, 566.6, 565.6, 564.6, 439.7, 437.6. UV / vis (CHCl 3 , C = 6.874×10 -5 M): λmax (ε) = 227 (5000), 248 (27700), 283 (5600 M –1 cm –1 ). ((2,4,6 - Tribromobenzene - 1,3,5 - triyl)tris(ethyne - 2,1 - diyl))tris(trimethylsilane)
[0097] 1,3,5-Tribromo-2,4,6-triiodobenzene 2 (346 mg, 0.5 mmol), [PdCl 2 (PPh 3 ) 2(105 mg, 0.15 mmol, 30 mol%), CuI (19 mg, 0.1 mmol, 20 mol%), Et3N (50 mL), and THF (40 mL) were added to a dry three-necked flask. Ethynyltrimethylsilane (736.7 mg, 1.07 mL, 7.5 mmol) and Ph 3 P (52 mg, 0.2 mmol, 40 mol%) were added to the mixture. The mixture was stirred at 80 °C under argon for 48 h. After removing the solvent on a rotary evaporator, DCM (100 mL) was added to the residue and filtered through diatomaceous earth. The mixture was washed with water (20 mL) and aqueous NaCl (20 mL), dried over anhydrous Na 2 SO 4 , and the solvent was removed under reduced pressure. The residue was further purified by flash chromatography using hexane as the eluent to give ((2,4,6-tribromobenzene-1,3,5-triyl)tris(ethyne-2,1-diyl))tris(trimethylsilane) 3 as a white solid (175 mg, 0.29 mmol, yield: 58%). Rf (hexane) = 0.3. Mp = 110 - 111 °C; FTIR (neat) νmax = 2958, 2160, 1376, 1340, 1245, 1019, 834, 758, 708, 658, 633, 539 cm -1 . 1 H NMR (500 MHz, CDCl 3 ): δ = 0.29 ppm [s, 27H, Si(CH 3 ) 3 . 13 C NMR (126 MHz, CDCl 3 ): δ 129.09 (CBr), 127.49 (C6C≡C), 106.79 (C≡CSi), 101.83 (C6C≡C), –0.23 [Si(CH3)3] ppm. 29 Si NMR (99 MHz, CDCl 3 ): δ -15.87 ppm. EI-MS fragmentation: m / z 603.9, 602, 601.9, 590.9, 589.9, 588.9, 588.9, 587.9, 586.9, 584.9. UV / vis (CHCl 3 , C = 5.436×10 -5 M): λmax (ε) = 260 (45700), 271 (44600), 289 (39600 M –1 cm –1 ). 1,3,5 - Tribromo - 2,4,6 - triethynylbenzene, TBTEB
[0098] To a solution of ((2,4,6-tribromobenzene-1,3,5-triyl)tris(ethyne-2,1-diyl))tris(trimethylsilane) (151 mg, 0.25 mmol) in THF (15 mL) was added 0.55 mL of TBAF (75% aqueous solution, 1.5 mmol), and the mixture was stirred at 0 °C for 15 min. Then the solution was diluted with ethyl acetate, washed with distilled water and dried over anhydrous Na 2 SO 4 4. The solvent was removed on a rotary evaporator. The residue was further purified by flash chromatography using hexane as the eluent to give TBTEB as a white solid (84 mg, 0.216 mmol, yield: 87%). Rf (hexane) = 0.2. FTIR (neat) νmax = 3275, 2922, 2112, 1519, 1368, 1336, 965, 736, 681, 634 cm -1 . 1 1H NMR (500 MHz, CDCl 3 3): δ = 5.16 (s, 3H, (C≡CH) ppm. 13 13C NMR (126 MHz, CDCl 3 3): 129.90 (CBr), 126.33 (C6C≡CH), 91.87 (C≡CH), 80.97 (C6C≡CH) ppm. EI-MS fragmentation: m / z 390.8, 389.9, 388.8, 387.8, 386.8, 385,8, 384,8, 383.8. UV / vis (CHCl 3 , C = 4.136×10 -5 -5 M): λmax (ε) = 212 (7100), 218 (8300), 260 (58100), 278 nm (33500 M –1 -1 cm –1 -1). Synthesis of carbon materials Table 1 - TBTEB a Representative polymerization reactions Entries [Pd] / mol% [Cu] / mol% Additive / mol% Solvent / base Temperature, °C Time, h Product 1 <![CDATA[Pd(PPh 3 ) 4 / 100%]]> CuI / 8% - Pyridine 110 72 High crystallinity 2 <![CDATA[Pd(PPh 3 ) 4 / 100%]]> <![CDATA[Cu foil 1 > - Pyridine 110 48 Low crystallinity 3 <![CDATA[Pd(PPh 3 ) 4 / 100%]]> - - Pyridine 110 72 Amorphous 4 - - - Pyridine 110 72 Amorphous 5 <![CDATA[PdCl 2 (PPh 3 ) 2 / 30%]]> Cu / Si <![CDATA[Ph 3 P / 40%]]> <![CDATA[THF / Et 3 N(44:56)]]> 80 48 Amorphous 6 - Cu / Si - Pyridine 110 72 Amorphous 7 - Cu wire - Pyridine 110 72 Amorphous 8 <![CDATA[Pd(PPh 3 ) 4 / 100%]]> Cu wire - Pyridine 110 72 Low crystallinity 9 - <![CDATA[Cu wire 1 > - Pyridine 100 72 Amorphous 10 <![CDATA[Pd(PPh 3 ) 4 / 40%]]> - - Pyridine 100 48 Amorphous 11 <![CDATA[Pd(PPh 3 ) 4 / 100%]]> Cu / Si - Pyridine 110 72 Amorphous 12 - <![CDATA[Cu foil 1 > - Pyridine 110 72 Amorphous 13 <![CDATA[PdCl 2 (PPh 3 ) 2 / 60%]]> Cu / Si <![CDATA[Ph 3 P / 80%]]> <![CDATA[THF / Et 3 N(1:1)]]> 80 72 Amorphous 14 - Cu foil - Pyridine 70 72 No material 1 The copper foil was sonicated in 3 M HCl, water, ethanol, and acetone for 20 min in sequence, dried under vacuum at room temperature and used immediately. a All reactions were carried out under a positive pressure of Ar (Schlenk line, with a Hg bubbler). General synthesis procedure of carbon materials
[0099] In a typical procedure, TBTEB, Pd(PPh 3 ) 4 and Cu are added to a Schlenk tube under an argon atmosphere, and a solvent is added. The tube is sealed, and the contents are degassed by three freeze-pump-thaw cycles. The reaction mixture is stirred and heated under an argon atmosphere for 72 hours. The reaction mixture is concentrated on a rotary evaporator. The solid product is washed with methanol, ethanol, isopropanol, toluene, hexane, ethyl acetate, and acetone. The washing procedure includes dispersing the material in the corresponding solvent by gentle sonication and then centrifuging. The conditions for the selected experiments in Table 1 are detailed below. Table 1, Entry 1
[0100] Using a general procedure, TBTEB (116 mg, 0.3 mmol), Pd(PPh 3 ) 4 (347 mg, 0.3 mmol), and CuI (4.6 mg, 0.024 mmol) are reacted in anhydrous pyridine (50 mL). After centrifugation and drying under a low vacuum (1 - 2 Torr) for over 10 hours, the typical mass of the crude product is about 90% of the monomer mass (104 mg for the above scale). After drying under a high vacuum (10 mTorr) for a long time and / or heating to 100 °C for 72 hours, the mass is reduced to about 60% of the original monomer mass (68 mg for the above scale). TLC indicates that the monomer conversion is quantitative. Table 1, Entry 2
[0101] TBTEB (116 mg, 0.3 mmol), Pd(PPh 3 ) 4 (347 mg, 0.3 mmol), and several copper foils are reacted in a mixture of anhydrous pyridine (50 mL) using a general procedure. Table 1, Entry 3
[0102] TBTEB (116 mg, 0.3 mmol) and Pd(PPh 3 ) 4 (347 mg, 0.3 mmol) are reacted in pyridine (50 mL) using a general procedure. Cu is not used. Table 1, Entry 4
[0103] TBTEB (116 mg, 0.3 mmol) is refluxed in pyridine (50 mL). Pd(PPh 3 ) 4 or copper is not used.
[0104] TBTEB was synthesized according to the reported procedure. Its reactivity was then screened under a series of conditions (Table 1). In the absence of a catalyst, TBTEB decomposed in refluxing pyridine with a half-life of approximately 24 h, yielding an amorphous carbonaceous material (Figure 22). Survey scans of X-ray photoelectron spectroscopy (XPS) indicated moderate loss of Br via spontaneous hydrodebromination reaction ( Figure 15 and 17D ). Similar featureless carbon was produced in the presence of Pd(PPh 3 ) 4 , although the Br loss was more significant ( Figure 14 and 17C ).
[0105] Experiments conducted in the simultaneous presence of Pd and Cu produced results that were dependent on the metal state. The Pd(II) precatalyst, along with PEPPSI-IPr (which was chosen by us because of its tendency for multi-site coupling), produced amorphous carbon that was roughly comparable to the control product. However, using stoichiometric Pd(PPh 3 ) 4 loaded in the presence of Cu foil, we obtained a black shiny material ( Figure 18B ). Transmission electron microscopy (TEM) images of this material revealed that the flakes consisted of stacked flat sheets (Figure 20). The layered morphology was confirmed by scanning electron microscopy (SEM) images of the flakes (Figure 24). Although there were distinct layers, Moiré patterns were not observed in the TEM. Selected area electron diffraction (SAED) experiments produced a spotty ring pattern ( Figure 20E -F), indicating randomly oriented sub-micron crystallites.
[0106] A product with higher crystallinity was obtained via an optimized homogeneous Pd(PPh 3 ) 4 / CuI protocol that allowed for efficient removal of contaminants. Survey scans of XPS of this product indicated that the levels of Pd and P contamination were below the detection limit of the technique ( Figure 12 ). We obtained high-resolution XPS data for the C1s region of this material ( Figure 2D ), as well as data for three controls: the product synthesized from Cu foil, the product from the Pd-only reaction, and the thermally reacted product ( Figure 12 ). The C1s peak could be deconvoluted into five sub-peaks corresponding to C-H (terminal alkyne sp 1 ), C≡C (internal alkyne sp 1 ), C=C (aromatic sp 2 ), aromatic C-Br, and C=O carbon. The contribution of C=O was negligible for all samples, indicating little oxidation under the reductive / anaerobic reaction conditions. There was no sp 1For the contributions of the sub-peaks, all fits did not converge, which strongly supports the presence of triple bonds in all products. XPS shows that the ratio of sp 3 ) 4 / CuI in the crystalline materials synthesized by the homogeneous Pd(PPh 1 and sp 2 carbons is 1:1, which is consistent with γ-graphyne. This ratio is much higher in the control samples ( Figure 16B -D), due to a large number of side reactions and contamination by aromatic impurities. The π-π* "shake up" peak at 290 eV is common in the XPS of graphite carbon, graphene, and small aromatic molecules. Notably, this peak does not appear in the XPS of graphdiyne. The "shake up" peak characteristics of the products of the homogeneous Cu protocol are negligible ( Figure 2D ), strongly indicating that the material is not graphite. This peak is significant in the control products also contaminated with P ( Figure 13 , 14 and 16C-D), suggesting that it may be related to the adsorbed PPh 3 .
[0107] We further explored the crystal structure and symmetry by electron diffraction. The spotty SAED patterns of the products obtained using the Pd(PPh 3 ) 4 / CuI protocol are clear and well-defined, consistent across different sample regions and independent of the size or presence of the selected area aperture. The near-perfect uniformity of the patterns indicates that the material consists of crystallites large enough to span the entire irradiated area (2×2 μm) of our typical imaging frame ( Figure 2B and 19), indicating that the crystallite size is at least 1-3 μm. The diffraction patterns observed from flat areas of the sample have perfect hexagonal symmetry ( Figure 3B ). Using the interatomic distances calculated by DFT, we constructed models of several possible stacking modes of γ-graphyne. These models were used to simulate the electron diffraction for c, b, and intermediate crystal orientations at an angle of approximately 45° to the (0001) polar axis (Figure 25). The simulated c-orientation patterns involve only the basal plane spacing ( Figure 24C and 24D ). The first- and second-order diffraction peaks (reflections) in the experimental diffraction patterns correspond to the and d-spacings, which match perfectly with the theoretical calculated spacings of the and and crystal plane groups of γ-graphyne ( Figure 3B and 3D)。These two distances are defined by the length of the alkyne bond. Some more symmetric space groups, such as Cmcm and R3m, are expected to produce diffraction patterns with systematic extinction. Since no such systematic extinction is observed in the diffraction patterns obtained, these space groups can be clearly excluded.
[0108] For another sample orientation, additional SAED patterns were obtained. The initial position of the sample stage was chosen to produce the most symmetric spot intensity distribution, which corresponds to the beam being perpendicular to the basal plane and coinciding with the a-axis. Then the sample was rotated about the b-axis. When the sample rotation reached approximately 45°, diffraction patterns involving the z-spacing began to appear. The experimental diffraction pattern for this orientation provided a group of closely spaced spots ( Figure 3C ), indicating the presence of defects in the layer stacking. Such defects do not appear in the c-orientation diffraction pattern because the stacking mode only affects the reflections involving the z-spacing (Figure 26). The symmetry of the pattern is consistent with our simulations for this intermediate orientation (Figures 25E, 25F, 25H). Since no systematic extinction was observed, we can exclude some of the more symmetric space groups, most notably the P6 3 mc space group. The experimental diffraction pattern is most consistent with a lower symmetry stacking mode such as P3 1 12 (Figure 25E) or an aperiodic superlattice. Notably, despite the multi-spot feature, the observed diffraction pattern does not indicate the presence of turbostratic stacking, which would produce a ring pattern. The shape factor effect changes the geometry of the diffracted beam, which introduces an error in the determination of the spot centers. However, the modeling results indicate that the diffraction pattern for the other sample orientation is consistent with an interlayer distance of approximately .
[0109] Our data indicate that the material we synthesized is multilayer γ-graphdiyne. Contrary to expectations, we found that no external template is required to synthesize highly crystalline γ-graphdiyne. Even in the reactions we carried out using Cu foil, there was no experimental evidence of any polymerization occurring on the surface. The reason for the lower crystallinity of the Cu foil product may be the reduced concentration of catalytic Cu species in the solution. Compared with the homogeneous Pd(PPh 3 ) 4 / CuI protocol, this led to slower Sonogashira coupling and a higher degree of side reactions.
[0110] We attempted to understand why TBTEB preferentially polymerizes into multilayer γ-graphdiyne flakes rather than an amorphous branched structure. Since the polymerization appears to be self-templated, we postulate that there are attractive supramolecular interactions between TBTEB and the γ-graphdiyne lattice. It has been demonstrated that various macrocyclic compounds and phenyleneethynylene oligomers related to the graphdiyne structure self-assembled through π-stacking driven by solvophobic effects. To explore the potential supramolecular interactions in our system, we calculated the structure and potential energy surface of a single TBTEB molecule binding to a γ-graphdiyne monolayer by DFT. Our calculated results predict that TBTEB will bind to the graphdiyne surface at two types of binding sites (around the aromatic ring and on the 12-DBA ring), with a binding energy exceeding 20 kcal / mol( Figure 27 ). The monomer species has a higher binding energy than toluene, and our calculated binding energy for it is approximately 11 kcal / mol. If each TBTEB species reacts when binding to the underlying γ-graphdiyne, it may result in one of many locally energy-minimized stacks or a mixed state thereof.
[0111] To our knowledge, the γ-graphdiyne we synthesized is the first instance of a spontaneously formed ordered covalent lattice under pure kinetic control. Typical covalent organic frameworks and metal-organic frameworks are held together by reversible bonds. This reversibility is considered crucial for continuous error correction during the reaction / crystallization process. Traditional views predict that the irreversible polymerization of A 3 B 3 -type monomers does not utilize strict geometric constraints in terms of reactivity and thus can only produce disordered branched structures. However, since we often observe micron-scale γ-graphdiyne crystallization, currently, crystallization-assisted two-dimensional polymerization must be kinetically more favorable than random three-dimensional growth. Additionally, the initial nucleation of planar graphdiyne sheets seems to be a highly probable event. The high fidelity of the generated lattice indicates that the system can correct errors despite the irreversibility of Sonogashira coupling. At the very least, the reaction must proceed with comparable efficiency at lattice edges and internal defect sites. Since "repairing" a single internal defect requires the formation of six new chemical bonds, these bond-forming steps are most likely kinetically coupled. The apparent error-correction ability and the strong dependence of the product structure on the nature of the palladium precatalyst strongly confirm our initial hypothesis regarding the multi-site coupling mechanism.
[0112] From the above description of the present invention, those skilled in the art will find improvements, changes, and modifications to the present invention. These improvements, changes, and modifications fall within the technical scope of those skilled in the art and shall be covered by the appended claims. The entire contents of all references, publications, and patents cited in this application are hereby incorporated by reference.
Claims
1. A method, comprising: synthesizing a covalently bonded lattice based on an irreversible bonding reaction that favors complete substitution on a polyfunctional substrate.
2. The method according to claim 1, wherein the bonding reaction is a Sonogashira cross-coupling reaction between a terminal alkyne and an aryl halide.
3. The method according to claim 2, wherein the reactant is any possible symmetric or asymmetric 1,3,5-trihalo-2,4,6-triethynylbenzene, wherein the halogen is any one of Cl, Br, or I.
4. The method according to claim 2, wherein the reactant is any possible symmetric or asymmetric ((2,4,6-trihalobenzene-1,3,5-triyl)tris(ethyne-2,1-diyl))tris(trimethylsilane), wherein the halogen is any one of Cl, Br, or I.
5. The method according to any one of claims 2 to 4, wherein the Sonogashira cross-coupling reaction is carried out using a palladium catalyst, and wherein the type of palladium source is selected from palladium black, palladium on carbon, palladium(π-cinnamyl) chloride dimer, bis(triphenylphosphine)palladium(II) dichloride, bis(benzonitrile)palladium(II) chloride, bis(triphenylphosphine)palladium(II) diacetate, tetrakis(triphenylphosphine)palladium(0), bis(dibenzylideneacetone)palladium(0), tris(dibenzylideneacetone)dipalladium(0), dichlorobis(tricyclohexylphosphine)palladium(II), dichlorobis(tri-o-tolylphosphine)palladium(II), allylpalladium(II) chloride dimer, (2-methylallyl)palladium(II) chloride dimer, (1,3-bis(2,6-diisopropylphenyl)imidazolidine)(3-chloropyridyl)palladium(II) dichloride, (1,3-bis(2,6-dimethylphenyl)imidazolidine)(3-chloropyridyl)palladium(II) dichloride, [1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene](3-chloropyridyl)palladium(II) dichloride, palladium(II) 2,4-pentanedionate, or any possible alkali metal salt of tris(3,3',3”-phosphinidynetris(benzenesulfonic acid)palladium(0).
6. The method according to any one of claims 2 to 5, wherein the Sonogashira cross-coupling reaction is carried out using a copper cocatalyst, and wherein the copper cocatalyst is selected from copper(I) iodide, copper(I) chloride, copper(I) bromide, copper(I) tetra(acetonitrile) hexafluorophosphate, copper(I) tetraacetonitrile trifluoromethanesulfonate, copper(0) foil or chips in combination with pyridine, copper(0) foil or chips in combination with any aliphatic tertiary amine, or copper(II) sulfate in combination with sodium ascorbate.
7. The method according to claim 6, wherein the reactant, palladium catalyst, and copper cocatalyst are provided in a solvent, and wherein the solvent is selected from pyridine, tetrahydrofuran, a mixture of tetrahydrofuran and N,N-diisopropylethylamine, toluene, benzene, water, or a biphasic mixture of water and an immiscible organic solvent.
8. The method according to claim 7, wherein the loading amount of the Pd catalyst is 0.5 mol% to 120 mol% relative to the 1,3,5-trihalo-2,4,6-triethynylbenzene monomer.
9. The method according to claim 7 or 8, wherein the loading amount of the Cu cocatalyst is 0.1 mol% to 10 mol% relative to the 1,3,5-trihalo-2,4,6-triethynylbenzene monomer.
10. The method according to any one of claims 1 to 9, wherein the reaction temperature is 60 °C to 130 °C.
11. The method according to claim 4, wherein the reaction conditions are any of the conditions listed in claims 5 to 10, and the reaction is carried out in the presence of a soluble fluoride salt.
12. The method according to any one of claims 1 to 11, wherein the ordered two-dimensional polymerization occurs in the absence of a physical substrate or an externally added template.
13. The method according to any one of claims 1 to 12, wherein the covalently bonded lattice comprises a sp 2 / sp 1 allotrope of carbon.
14. The method according to any one of claims 1 to 13, wherein the covalently bonded lattice comprises graphdiyne.
15. The method according to any one of claims 1 to 14, wherein the covalently bonded lattice comprises γ-graphdiyne.
16. The method according to any one of claims 1 to 15, wherein the obtained multilayer γ-graphdiyne has a linear dimension of the crystal domain in the range of 10 nanometers to 500 micrometers.
17. The method according to any one of claims 1 to 16, wherein the obtained few-layer (1 - 25 layers) γ-graphdiyne has a linear dimension of the crystal flake in the range of 10 nanometers to 500 micrometers.
18. A method comprising: synthesizing a covalently bonded lattice based on an irreversible bonding reaction that favors complete substitution on a multifunctional substrate, wherein the ordered two-dimensional polymerization occurs in the absence of a physical substrate or an externally added template.
19. The method according to claim 18, wherein the bonding reaction is a Sonogashira cross-coupling reaction between a terminal alkyne and an aryl halide.
20. The method according to claim 19, wherein the reactant is any possible symmetric or asymmetric 1,3,5-trihalo-2,4,6-triethynylbenzene, wherein the halogen is any one of Cl, Br, or I.
21. The method according to claim 19, wherein the reactant is any possible symmetric or asymmetric ((2,4,6-trihalobenzene-1,3,5-triyl)tris(ethyne-2,1-diyl))tris(trimethylsilane), wherein the halogen is any one of Cl, Br, or I.
22. The method according to any one of claims 19 to 21, wherein the Sonogashira cross-coupling reaction is carried out using a palladium catalyst, and wherein the type of palladium source is selected from palladium black, palladium on carbon, palladium(π-cinnamyl) chloride dimer, bis(triphenylphosphine)palladium(II) dichloride, bis(benzonitrile)palladium(II) chloride, bis(triphenylphosphine)palladium(II) diacetate, tetrakis(triphenylphosphine)palladium(0), bis(dibenzylideneacetone)palladium(0), tris(dibenzylideneacetone)dipalladium(0), dichloro-bis(tricyclohexylphosphine)palladium(II), dichloro-bis(tri-o-tolylphosphine)palladium(II), allylpalladium(II) chloride dimer, (2-methylallyl)palladium(II) chloride dimer, (1,3-bis(2,6-diisopropylphenyl)imidazolidin-2-ylidene)(3-chloropyridyl)palladium(II) dichloride, (1,3-bis(2,6-dimethylphenyl)imidazolidin-2-ylidene)(3-chloropyridyl)palladium(II) dichloride, [1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene](3-chloropyridyl)palladium(II) dichloride, palladium(II) 2,4-pentanedionate, or any possible alkali metal salt of tris(3,3',3”-phosphinidynetris(benzenesulfonic acid)palladium(0).
23. The method according to any one of claims 19 to 22, wherein the Sonogashira cross-coupling reaction is carried out using a copper cocatalyst, and wherein the copper cocatalyst is selected from copper(I) iodide, copper(I) chloride, copper(I) bromide, tetra(acetonitrile)copper(I) hexafluorophosphate, tetraacetonitrilecopper(I) trifluoromethanesulfonate, copper(0) foil or chips in combination with pyridine, copper(0) foil or chips in combination with any aliphatic tertiary amine, or copper(II) sulfate in combination with sodium ascorbate.
24. The method according to claim 23, wherein the reactants, palladium catalyst, and copper cocatalyst are provided in a solvent, and wherein the solvent is selected from pyridine, tetrahydrofuran, a mixture of tetrahydrofuran and N,N-diisopropylethylamine, toluene, benzene, water, or a biphasic mixture of water and an immiscible organic solvent.
25. The method according to claim 24, wherein the loading of the Pd catalyst is from 0.5 mol% to 120 mol% relative to the 1,3,5-trihalo-2,4,6-triethynylbenzene monomer.
26. The method according to claim 24 or 25, wherein the loading of the Cu cocatalyst is from 0.1 mol% to 10 mol% relative to the 1,3,5-trihalo-2,4,6-triethynylbenzene monomer.
27. The method according to any one of claims 18 to 26, wherein the reaction temperature is from 60 °C to 130 °C.
28. The method according to claim 21, wherein the reaction conditions are any of the conditions listed in claims 22 to 27, and the reaction is carried out in the presence of a soluble fluoride salt.
29. The method according to any one of claims 18 to 29, wherein the covalently bonded lattice comprises a sp 2 / sp 1 allotrope of carbon.
30. The method according to any one of claims 18 to 30, wherein the covalently bonded lattice comprises graphdiyne.
31. The method according to any one of claims 18 to 30, wherein the covalently bonded lattice comprises γ-graphyne.
32. The method according to any one of claims 18 to 31, resulting in a multi-layer γ-graphyne, the linear dimension of the crystal domains of which is in the range of 10 nanometers to 500 micrometers.
33. The method according to any one of claims 18 to 32, resulting in few-layer (1 - 25 layers) γ-graphyne, the linear dimension of the crystal flakes of which is in the range of 10 nanometers to 500 micrometers.
34. Graphyne prepared by the method according to any one of claims 1 to 33.
35. The graphyne according to claim 34, which has near-perfect crystal uniformity and / or near-perfect hexagonal crystal symmetry.
36. The graphyne according to claim 35, which has few or no crystal defects.
37. The graphdiyne according to claim 35, wherein the ratio of sp 1 carbon to sp 2 carbon in the crystal material is 1:
1.
38. γ-Graphyne, the linear dimension of the crystal domains of which is in the range of 10 nanometers to 500 micrometers.
39. The γ-graphyne according to claim 38, comprising multi-functional reactive groups on the edges of the γ-graphyne.
40. The γ-graphyne according to claim 38, wherein the multi-functional reactive groups are selected from alkyne and halogen groups.
Citation Information
Cited By
Acetylene-pyridyl organic polymer photocatalyst as well as preparation method and application thereof
CN120842547A